1998
DOI: 10.3168/jds.s0022-0302(98)75679-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Systematic Breeding Programs for Lactating Dairy Cows: A Review

Abstract: Observing cows in estrus and inseminating them at the optimum time are necessary steps for effective reproductive management of a dairy herd. However, larger herd sizes can lead to reproductive inefficiency and decreased profits on dairy farms. Synchronization of estrus behavior through pharmacological control has been used to improve reproductive efficiency. Methods of synchronizing estrus were originally devised to decrease the time spent detecting estrus; however, systematic breeding programs are now being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 24 publications
3
49
0
4
Order By: Relevance
“…This might have been one of the causes of the low conception rate. Previous studies also reported that the conception rate at 50 to 75 d postpartum at initiation of Ovsynch was lower than the figure at 76 d postpartum [57,58].…”
Section: Factors Affecting the Conception Rate After Ovsynch/ Taimentioning
confidence: 96%
“…This might have been one of the causes of the low conception rate. Previous studies also reported that the conception rate at 50 to 75 d postpartum at initiation of Ovsynch was lower than the figure at 76 d postpartum [57,58].…”
Section: Factors Affecting the Conception Rate After Ovsynch/ Taimentioning
confidence: 96%
“…Well managed and profitable dairy farming requires animal with good reproductive performance (Nebel and Jobst, 1998). However, various reports of decreasing profit in dairy farming have been identified where improvements can be made (Bishop, 1964).…”
Section: Introductionmentioning
confidence: 99%
“…In our country, dairy can be an important sector for rural development and poverty alleviation. Reproductive efficiency is essential for profitable dairy farms (Nebel and Jobst, 1998). Economy of dairy farming largely depends on good conception rates after insemination.…”
Section: Introductionmentioning
confidence: 99%